Motivation and demotivation over two years: A case study of English language learners in Japan - Kikuchi, Keita (Studies in Second Language Learning and Teaching, 2019)
This paper is about four Japanese university students majoring in international studies, who participated in a two-year study examining changes in their motivation. Using monthly interviews and a 29-item questionnaire on Dörnyei’s (2005) L2 motivational self system that was administered alongside each interview, the trajectories of learner motivation were investigated, based on both quantitative and qualitative data. First, changes in the participants’ motivation were identified using quantitative data. Next, a variety of motivators and demotivators that learners experienced both inside and outside of their classrooms were analyzed using the qualitative data. With the data obtained, this study focuses on how four learners’ language learning motivation and contexts adapt to each other, and how the dynamics of the four learners’ motivation changes due to their learning experiences. Each learner was different in their trajectory of motivation and the kinds of motivators and demotivators that they experienced in their particular contexts. The four learners underwent unique motivators and demotivators, and reacted differently. While participants identified their ideal L2 selves, or ought-to L2 selves, these self-guides were not strengthened by their L2 experiences over time. Based on these findings, the importance of studying the rich experiences of language learners in motivation research is discussed.